High-efficient C3N4-viologen charge transfer systems for promoting photocatalytic H2 evolution through band engineering. (19th May 2023) - Sui, Qi; Li, Runjie; Zhang, Yanyan; Huang, Mengtian; Wang, Ting; Yang, Man; Cao, Miao; Hong, Xiaoping; Li, Benxia
Abstract: Accelerating the charge transfer (CT) capability of photocatalysts is an efficient way to improve the overall photocatalytic performance, yet the precise regulation of CT in photocatalyst systems is still lacking. In this paper, a series of hybrid photocatalysts composed of graphitic carbon nitride (CN ) and various viologens (V ) were prepared for the photocatalytic hydrogen evolution (PHE) from water splitting under visible-light irradiation. Considering the fixed energy structure of CN, the different electron-withdrawing substituents were introduced to engineer the band structure of V delicately and modulate the CT process between CN and V . It was shown that all the hybrid photocatalysts CN-x%V y exhibited higher photocatalytic performance, of which CN–1%V 3, possessing the strongest electron withdrawing group (-NO2 ), demonstrated the best PHE performance (3572.3 μmol g −1  h −1 ), exceeding 29 times over the unmodified CN . It was proposed that the introduction of V can optimize the interfacial photogenerated electron transfer (CN →V →Pt) of the whole photocatalytic system effectively. We highlighted the V as an efficient chemical segment to modify semiconductors toward enhanced activity due to the following unique characteristics: (i) the unique redox ability, (ii) the easy synthetic methods for controlling the band structures precisely, and (iii) the inherent positively charged feature. This work provides a deep understanding of CT for the rational design of high-performance photocatalysts through band engineering. Graphical abstract: Image 1 Highlights: Hybrid photocatalysts CN-x%V y composed of g -C3 N4 (CN ) and viologens (V ) were prepared. The photocatalytic performance of CN-x%V y catalysts was dependent on the band engineering of V. Charge transfer of CN-x%V y catalysts was precisely regulated. CN–1%V 3 exhibited a 29 times higher photocatalytic H2 evolution rate than the unmodified CN.